pH-Responsive Polyketone/5,10,15,20-Tetrakis-(Sulfonatophenyl)Porphyrin Supramolecular Submicron Colloidal Structures - Araya-Hermosilla, Esteban (Polymers (Basel), 2020)
In this work, we prepared color-changing colloids by using the electrostatic self-assembly approach. The supramolecular structures are composed of a pH-responsive polymeric surfactant and the water-soluble porphyrin 5,10,15,20-tetrakis-(sulfonatophenyl)porphyrin (TPPS). The pH-responsive surfactant polymer was achieved by the chemical modification of an alternating aliphatic polyketone (PK) via the Paal–Knorr reaction with N-(2-hydroxyethyl)ethylenediamine (HEDA). The resulting polymer/dye supramolecular systems form colloids at the submicron level displaying negative zeta potential at neutral and basic pH, and, at acidic pH, flocculation is observed. Remarkably, the colloids showed a gradual color change from green to pinky-red due to the protonation/deprotonation process of TPPS from pH 2 to pH 12, revealing different aggregation behavior.